Incidence of Burnout and its Relationship with Musculoskeletal Disorders among Healthcare College Students in Lahore, Pakistan - Tamkanat Ilyas, Mamoona Anwar, Muhammad Nouman Tabassum, Sania Maqbool, Quratulain, Madiha Asghar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Burn-out is a syndrome defined as the result of chronic workplace stress that has not been successfully managed. It has three dimensions: 1) energy depletion or exhaustion 2) feelings of negativism about one’s job3) reduced professional efficacy. Burn-out& musculoskeletal disorders (MSD) are the most common health problem associated with work in Europe, affecting millions of workers. Several studies have found a high prevalence of burnout among medical and dental students. Aim: To determine the prevalence of burnout syndrome & its association with MSK disorders among health care students of Lahore, Pakistan. Methods: This was a cross sectional survey among 259 students from different health care colleges studied in different semesters using the sample of convenience. The Nordic Musculoskeletal Questionnaire&Mashlach burnout inventory questionnaire were used for data collection. Results: The frequency and percentage of our outcome according to the report, 149 of the total students and 57.5% of respondents have neck disorder. Due to burnout during their medical studies, 50 students (19.3% of respondents) have shoulder problems, and 59 students (22.8% of our sample size) have upper back problems. There are 40 students with mild neck pain among the 259 students, 86 students with moderate neck disorder, 23 students with severe neck disorder, and 149 students with no neck disorder. There were 50 students with shoulder disorders and 59 with upper back disorders in total. As a result of burnout, the majority of students suffer from neck disorders. Pearson Chi square test value is 13. it shows the validity of research as it is more than 5. The majority of the participants shows high levels of emotional exhausation ,desperation& low occupational effectiveness .This suggests if preventions are not taken & interventional strategies not guided , there will be symptom progression & reduced professional effectiveness may occur among targeted population Conclusion: There is a strong association between B.O and MSD. The cervical and neck area is more prevalent then the upper back and shoulder , out of 259 students 149 suffer from neck pain. Keywords: Burnout syndrome , MSD/musculoskeletal disorder, WMDs/work related musculoskeletal disorders.